2013
DOI: 10.1016/j.amjcard.2013.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Phenotype of the Failing Fontan in an Adult Population

Abstract: Fontan failure can occur even with normal systolic ventricular function and often in the context of significant liver disease. We hypothesized that Fontan failure is hemodynamically distinct from traditional heart failure and characterized by low systemic vascular resistance (SVR) index and preserved cardiac index. Twenty-seven symptomatic adult Fontan (SAF) patients who underwent catheterization from 2001 to 2011 constituted our study group. Fifty-four predominantly asymptomatic pediatric Fontan (PF) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 29 publications
(35 reference statements)
1
69
1
Order By: Relevance
“…19 In the current study, we did not observe any significant difference in the systemic vascular resistance between Groups 1 and 2. A possible explanation for the observed difference between our data and that of the Hebson et al study again may relate to a higher prevalence of liver disease in their cohort as well, which decreases systemic vascular resistance independent of cardiac status for the reasons outlined above.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…19 In the current study, we did not observe any significant difference in the systemic vascular resistance between Groups 1 and 2. A possible explanation for the observed difference between our data and that of the Hebson et al study again may relate to a higher prevalence of liver disease in their cohort as well, which decreases systemic vascular resistance independent of cardiac status for the reasons outlined above.…”
Section: Discussioncontrasting
confidence: 50%
“…In a different study, Hebson et al 19 reported that symptomatic Fontan patients had lower systemic vascular resistance in comparison to asymptomatic patients. 19 In the current study, we did not observe any significant difference in the systemic vascular resistance between Groups 1 and 2.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is considerable concern over long-term deterioration of clinical state and ventricular performance in older Fontan patients [2,4,5]. Other remaining questions with regard to ventricular function in this population include the role of ventricular anatomy (left vs. right type ventricular dominance), the impact of more recent strategies towards staging and timing of the TCPC and the differences resulting from different surgical techniques available for this operation [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, failure has been defined in pediatric literatures as the development of protein-losing enteropathy, hospitalization, ventricular failure, and exercise intolerance to name a few. While risk factors associated with pediatric Fontan failure may help to identify the poorly functioning Fontan circulation in children and adolescents, caution must be exercised when applying this model to the adult population with distinct hemodynamics and prevalent end-organ manifestations [4].…”
mentioning
confidence: 99%